Kebijakan Indonesia terhadap Anak sebagai Pelaku Tindak Pidana Penyalahgunaan Narkotika - Cokorda Istri Agung Indira Rahayu; I Wayan Novy Purwanto (CV Rewang Rencang, 2025)
This article aims to analyze drug abuse committed by juveniles. With the results of the research;. There are several factors that cause juveniles to commit criminal acts of narcotics abuse. These factors are inseparable from the influence of the environment and from within the child (internal factors and external factors). Furthermore, during the criminal justice process against juveniles who commit criminal acts of narcotics abuse, diversion must first be pursued as an attempt at legal protection and a form of legal responsibility for juvenile drug abusers, in order to avoid children from the adverse effects of the criminal justice process.